2012
DOI: 10.1016/j.jneb.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Feasibility of a Digital Diet Estimation Method for Use with Preschool Children: A Pilot Study

Abstract: Objective The goal of the study was to assess the validity and feasibility of a digital diet estimation method for use with preschool children in Head Start. Methods Preschool children and their caregivers participated in validation (n = 22) and feasibility (n = 24) pilot studies. Validity was determined in the metabolic research unit using actual gram weight measurements as the reference method. Feasibility of using the digital diet estimation method was determined in Head Start and in the home by assessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 26 publications
3
56
0
Order By: Relevance
“…Concerning cafeteria products, the photographic method estimates food intake by adults and children of preschool age quite precisely (Martin et al, 2014;Nicklas et al, 2012). Validation studies regarding this method showed it can be very exact in the estimation of food intake both for groups and individuals (Martin et al, 2014).…”
Section: Figure 1 Energy Intake In Training and Match Day Vs Recommmentioning
confidence: 99%
“…Concerning cafeteria products, the photographic method estimates food intake by adults and children of preschool age quite precisely (Martin et al, 2014;Nicklas et al, 2012). Validation studies regarding this method showed it can be very exact in the estimation of food intake both for groups and individuals (Martin et al, 2014).…”
Section: Figure 1 Energy Intake In Training and Match Day Vs Recommmentioning
confidence: 99%
“…Using naturalistic settings and photographs in measuring young children's food choices and intake is gaining popularity and has been found to be a valid and feasible research method (27)(28)(29) .…”
Section: Introductionmentioning
confidence: 99%
“…Digital photographic assessments have been employed in studies on dietary intake in military recruits during basic training 18 and in both pre-school 19 and elementary school children; 20 however, evidence for the validity of these methods is limited. With the exception of the Remote Food Photography method described by Martin et al, 21 which uses a smartphone to capture food images and plate waste, validity for the other digital photographic approaches has been established by comparing estimates of food weight by digital photography vs. measured food weight of test meals in a laboratory setting 18,19 or against weighed food records over 1 to 7 days 22 rather than against a biomarker of energy expenditure, such as doubly labelled water in free-living individuals.…”
Section: Introductionmentioning
confidence: 99%